Microwave sintering of pure and TiO2 doped MgAl2O4 ceramic using calibrated, contactless in-situ dilatometry. Issue 15 (15th November 2016) - Macaigne, Rodolphe; Marinel, Sylvain; Goeuriot, Dominique; Meunier, Christophe; Saunier, Sébastien; Riquet, Guillaume
Abstract: This work describes the development of a contactless dilatometry system for simultaneously measuring the shrinkage and the temperature during microwave sintering of materials in a 2.45 GHz single-mode cavity. An original temperature calibration method has been developed using a monochromatic Infrared pyrometer, taking into account that the apparent emissivity depends on the temperature. Different calibration oxide materials were selected according to their melting points to determine the temperature dependence of the thermal emissivity. This parameter was then used to get the most accurate temperature values over the entire processing temperature range. Afterwards, microwave sintering kinetics and microstructures of pure MgAl2 O4 and TiO2 -doped spinel material were studied and compared to those of conventionally sintered samples. It was shown that there was no significant difference in the densification behavior of the pure spinel material compared to the conventionally sintered material. On the contrary, the shrinkage curve of the microwave sintered TiO2 -doped spinel was found to be shifted to lower temperature compared to the conventional shrinkage curve. This result occurs due to likely species diffusivity enhancement provided by a specific coupling between microwaves and point defects, such as [Ti 4+ - V Mg ′ ′ ] pair dipoles.